Case 3765: Thionia Stål, 1859 (Hemiptera, Auchenorrhyncha, Issidae): proposed designation of Issus cinctifrons Stål, 1854 as the type species. - Gnezdilov, Vladimir M; Dmitriev, Dmitry A (Bulletin of Zoological Nomenclature)
Noticed BZN 75 (31 May 2018): 2. Closed BZN 76 (30 April 2019): 97.